2018
DOI: 10.3389/fimmu.2018.02121
|View full text |Cite
|
Sign up to set email alerts
|

Tc17/IL-17A Up-Regulated the Expression of MMP-9 via NF-κB Pathway in Nasal Epithelial Cells of Patients With Chronic Rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is a common chronic inflammatory disease of the upper airways involving nasal cavity and sinus. Deriving both from its clinical complexity with protean clinical manifestations as well its pathogenetic heterogeneity, the molecular mechanisms contributing to the pathogenesis of CRS remain unclear, and attract a wide interest in the field. Current evidences indicate that IL-17A is highly expressed in chronic rhinosinusitis with nasal polyps (CRSwNP). However, its pathogenetic role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 67 publications
2
49
0
Order By: Relevance
“…The EMT process is driven by an array of factors such as WNT, reactive oxygen species, proteases, HIF1, IL-13 Epiregulin, Oncostatin M, and IL-1 (Oyer et al, 2013;Batzakakis et al, 2014;Schleimer, 2017;Aazami et al, 2018;Yang et al, 2018;Tomaszewska et al, 2019). CRSwNP patients have altered expression levels of EMT related factors, such as MMP-1 (Malinsky et al, 2013;Homma et al, 2017), MMP-2 (Malinsky et al, 2013), TIMP-1 (Wang et al, 2012;Muluk et al, 2015), MMP-7 (Yang et al, 2017;Chen et al, 2018), MMP-9 (Wang et al, 2012;Malinsky et al, 2013;Yeo et al, 2013;Li et al, 2015;Muluk et al, 2015;Chen et al, 2018;Suzuki et al, 2018;Xiang et al, 2019), TIMP-2 (Li et al, 2015) E-cadherin (Hupin et al, 2014;Kim et al, 2018;Deng et al, 2019). BMT is associated with duration of inflammation independent of tissue eosinophilia (Kountakis et al, 2004;Kuhar et al, 2017).…”
Section: Upper Airway Epithelial Functions During Ar and Crsmentioning
confidence: 99%
“…The EMT process is driven by an array of factors such as WNT, reactive oxygen species, proteases, HIF1, IL-13 Epiregulin, Oncostatin M, and IL-1 (Oyer et al, 2013;Batzakakis et al, 2014;Schleimer, 2017;Aazami et al, 2018;Yang et al, 2018;Tomaszewska et al, 2019). CRSwNP patients have altered expression levels of EMT related factors, such as MMP-1 (Malinsky et al, 2013;Homma et al, 2017), MMP-2 (Malinsky et al, 2013), TIMP-1 (Wang et al, 2012;Muluk et al, 2015), MMP-7 (Yang et al, 2017;Chen et al, 2018), MMP-9 (Wang et al, 2012;Malinsky et al, 2013;Yeo et al, 2013;Li et al, 2015;Muluk et al, 2015;Chen et al, 2018;Suzuki et al, 2018;Xiang et al, 2019), TIMP-2 (Li et al, 2015) E-cadherin (Hupin et al, 2014;Kim et al, 2018;Deng et al, 2019). BMT is associated with duration of inflammation independent of tissue eosinophilia (Kountakis et al, 2004;Kuhar et al, 2017).…”
Section: Upper Airway Epithelial Functions During Ar and Crsmentioning
confidence: 99%
“…Western blotting was performed as reported previously. [13] The PVDF membranes were rst incubated with primary antibodies MMP-9 (1:1000; Abcam, Cambridge, UK), pERK, ERK, pIκBα, IκBα (1:1000; Cell Signaling Technology, Boston, USA), and GAPDH (1:3000; PeproTech, Rocky Hill, USA) overnight at 4 °C separately, and then incubated with HRP-conjugated secondary antibody (Bioworld, Nanjing, China). Color development was achieved by ECL reagents.…”
Section: Western Blotmentioning
confidence: 99%
“…[10] However, MMP-1, MMP-2, and MMP-3 expression in patients with CRS is controversial, whereas several studies have reported MMP-7 and MMP-9 levels to be higher in cases with CRSwNP. [11][12][13][14] Overall, the detailed upstream modulation of MMPs promoting tissue remodeling in chronic sinusitis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a relationship between CRSwNP and the NF-κB pathway. (Chen et al, 2018;Jung et al, 2019). Chen et al found that interleukin (IL)-17A upregulated the expression of matrix metalloproteinase (MMP)-9 via the NF-κB pathway in nasal epithelial cells (Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Chen et al, 2018;Jung et al, 2019). Chen et al found that interleukin (IL)-17A upregulated the expression of matrix metalloproteinase (MMP)-9 via the NF-κB pathway in nasal epithelial cells (Chen et al, 2018). Jung et al showed that p65 NF-κB and NF-κB-related in ammatory cytokines were expressed in both eosinophilic and non-eosinophilic nasal polyps.…”
Section: Introductionmentioning
confidence: 99%